A randomized clinical trial evaluating the efficacy and safety of the once-weekly dipeptidyl peptidase-4 inhibitor omarigliptin in patients with type 2 diabetes inadequately controlled on metformin monotherapy. (3rd October 2017) - Shankar, R. Ravi; Inzucchi, Silvio E.; Scarabello, Victoria; Gantz, Ira; Kaufman, Keith D.; Lai, Eseng; Ceesay, Paulette; Suryawanshi, Shailaja; Engel, Samuel S.
Abstract: Objective: To examine the efficacy and safety of the once-weekly (q.w.) dipeptidyl peptidase-4 inhibitor, omarigliptin, in patients with type 2 diabetes (T2DM) and inadequate glycemic control on metformin monotherapy. Methods: In a randomized, double-blind trial, patients with T2DM on a stable dose of metformin monotherapy (≥1500 mg/day) with glycated hemoglobin (HbA1c) of 7.0–10.5% were randomized to omarigliptin 25 mg q.w. or matching placebo ( n  = 201 in both) for 24 weeks (primary timepoint) followed by an additional 80-week treatment period. Results: At week 24, from a mean baseline HbA1c of 8.0–8.1%, the least squares (LS) mean (95% CI) change from baseline in HbA1c (primary end-point) was –0.54% (–0.69%, –0.40%) in the omarigliptin group and 0.00% (–0.14%, 0.15%) in the placebo group, for a between-group difference of –0.55% (–0.75%, –0.34%); p  < .001. Between-group differences (LS mean 95% CI) for the secondary end-points of 2-h post-meal glucose and fasting plasma glucose (omarigliptin vs placebo) were –0.8 mmol/L (–1.4, –0.2) ( p  = .011) and –0.5 mmol/L (–0.9, –0.1) ( p  = .010), respectively. At week 24, the incidences of symptomatic hypoglycemia and subjects with one or more adverse event (AE), serious AEs, and discontinuations due to an AE were similar in the omarigliptin and placebo groups. Over 104 weeks, omarigliptin treatment provided a clinically meaningful reduction in HbA1c. Conclusions: In patients with T2DM, adding omarigliptin 25 mg q.w. to metformin monotherapy improved glycemic control over 104 weeks and was generally welltolerated with a low risk of hypoglycemia.